Five-year antibody persistence in children after one dose of inactivated or live attenuated hepatitis A vaccine. Issue 6 (3rd June 2017) - Zhang, Zhilun; Zhu, Xiangjun; Hu, Yuansheng; Liang, Miao; Sun, Jin; Song, Yufei; Yang, Qi; Ji, Haiquan; Zeng, Gang; Song, Lifei; Chen, Jiangting
ABSTRACT: In China, both inactivated hepatitis A (HA) vaccine and live attenuated HA vaccine are available. We conducted a trial to evaluate 5-year immune persistence induced by one dose of inactivated or live attenuated HA vaccines in children. Subjects with no HA vaccination history had randomly received one dose of inactivated or live attenuated HA vaccine at 18–60 months of age. Anti-HAV antibody concentrations were measured before vaccination and at the first, second, and fifth year after vaccination. Suspected cases of hepatitis A were monitored during the study period. A total of 332 subjects were enrolled and 182 provided evaluable serum samples at all planned time points. seropositive rate at 5 y was 85.9% in the inactivated HA vaccine group and 90.7% in the live attenuated HA vaccine group. GMCs were 76.3% mIU/ml (95% CI: 61.7 – 94.4) and 66.8mIU/ml (95% CI: 57.8 – 77.3), respectively. No significant difference in antibody persistence between 2 groups was found. No clinical hepatitis A case was reported. A single dose of an inactivated or live attenuated HA vaccine at 18–60 months of age resulted in high HAV seropositive rate and anti-HAV antibody concentrations that lasted for at least 5 y.